Bolzano, Bernard, "Erbauungsreden des Studienjahres 1817/18, Teilband 1", hg. v. Kurt F. Strasser (Bernard Bolzano-Gesamtausgabe, Reihe II.A.23,1), Fromman-Holzboog Verlag: Stuttgart-Bad Cannstatt 2015 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

von Plato, Jan, “Kurt Gödel’s First Steps in Logic: Formal Proofs in Arithmetic and Set Theory Through a System of Natural Deduction”, In: The Bulletin of Symbolic Logic 24 (2018), 319–335 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Erbauungsreden des Studienjahres 1817/18, Teilband 2", hg. v. Kurt F. Strasser (Bernard Bolzano-Gesamtausgabe, Reihe II.A.23,2), Fromman-Holzboog Verlag: Stuttgart-Bad Cannstatt 2015 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Briefwechsel mit Franz Exner, 1833–1844", hg. v. Edgar Morscher (Bernard Bolzano-Gesamtausgabe, Reihe III.23,1), Fromman-Holzboog Verlag: Stuttgart-Bad Cannstatt 2017 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Schubring, Gert, “Searches for the Origins of the Epistemological Concept of Model in Mathematics”, In: Archive for History of Exact Sciences 71 (2017), 245–278 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sprachgebrauch und Sprachwechsel an der Lemberger Universität im ausgehenden 18. und in der ersten Hälfte des 19. Jahrhunderts - Ptashnyk, Stefaniya (Vernakuläre Wissenschaftskommunikation. Beiträge zur Entstehung und Frühge-schichte der modernen deutschen Wissenschaftssprachen (Lingua Academica 1) (Handbuchartikel))

Die Rolle der deutschen Sprache im österreichischen und im polnischen Galizien - Ptashnyk, Stefaniya (Galizien und die Galiziendeutschen (1914–1940))

Denkstile in der deutschen Sprachwissenschaft: Bausteine einer Fachgeschichte aus dem Blickwinkel der Wissenschaftstheorie Ludwik Flecks - Ptashnyk, Stefaniya (Wissenschaftlicher Literaturanzeiger 2019 (online))

„Tagung ‚Historisches Codeswitching mit Deutsch‘“. Tagungsbericht - Ptashnyk, Stefaniya; Prinz, Michael (Jahrbuch 2017 der Heidelberger Akademie der Wissenschaften)

"Walsdorf, Ariane; Baldur, Klaus; Stein, Erwin; Kopp, Fran Otto, Das letzte Original. Die Leibniz-Rechenmaschine der Gottfried Wilhelm Leibniz Bibliothek", hg. v. der Gottfried Wilhelm Leibniz Bibliothek, Hannover 2014 - Peckhaus, Volker (Mathematical Reviews)

Griffin, Nicholas, “Russell and Leibniz on the Classification of Propositions”, in: R. Krömer, Y. Chin-Drian (eds.), New Essays on Leibniz Reception, Birkhäuser/Springer: Basel 2012, 87–127 - Peckhaus, Volker (Mathematical Reviews)

Siegmund-Schultze, Reinhard, “Pulling Harriot Out of Newton’s Shadow: How the Norwegian Outsider Johannes Lohne Came to Contribute to Mainstream History of Mathematics”, in V.R. Remmert et al. (Hgg.), Historiography of Mathematics in the 19th and 20th Centuries, Birkhäuser/Springer: Cham 2016 (Trends in the History of Science), 219–243 - Peckhaus, Volker (Mathematical Reviews)

Cohen, H. Floris, “The ‘Mathematization of Nature’: The Making of a Concept, and How It Has Fared in Later Years”, in V.R. Remmert et al. (Hgg.), Historiography of Mathematics in the 19th and 20th Centuries, Birkhäuser/Springer: Cham 2016 (Trends in the History of Science), 143–160 - Peckhaus, Volker (Mathematical Reviews)

Delarivière, Sven; Van Kerkhove, Sven, “The ‘Artificial Mathematician’ Objection: Exploring the (Im)possibility of Automating Mathematical Understanding”, in: B. Sriraman (Hg.), Humanizing Mathematics and its Philosophy, Birkhäuser/Springer: Cham 2017, 173–193 - Peckhaus, Volker (Mathematical Reviews)

Bennett, Deborah, “Origins of the Venn Diagram”, in: M. Zack/E. Landry (Hgg.), Research in History and Philosophy of Mathematics, Birkhäuser/Springer: Cham 2015 (Proceed. Canad. Soc. Philos. Math.), 105–109 - Peckhaus, Volker (Mathematical Reviews)

Maat, Jaap, “Leibniz”, in: Alex Malpass/Marianna Antonutti Morfori (Hgg.), The History of Philosophical and Formal Logic: From Aristotle to Tarski, Bloomsbury Academic: London 2017, 101–119 - Peckhaus, Volker (Mathematical Reviews)

Luciano, Erika, “Characterizing a Mathematical School: Shared Knowledge and Peano’s Formulario”, In: Revue d’Histoire des Mathématiques 23 (2017), 183–231 - Peckhaus, Volker (Mathematical Reviews)

Centrone, Stefania, "Studien zu Bolzano", Academia: Sankt Augustin 2015 (Beiträge zur Bolzano-Forschung; 26) - Peckhaus, Volker (Mathematical Reviews)

Reconsidering interiorization: Self moving across language spacetimes - Bertau, Marie-Cécile; Karsten, Andrea (New Ideas in Psychology)
Sociogenesis addresses a pervasive problem in psychology given by Cartesian dualism that assigns the mental an inner locus apart from material activity. Aligning ourselves to the ongoing critical discussions of interiorization in psychology, we explore the crucial notion of space by highlighting language as sociocultural and dialogical activity performed by other-oriented individuals. We discuss space in terms of the “language spacetime”, a symbolic, embodied formation of mutually positioned speaking and listening selves. This leads beyond the “inside-outside” container metaphor and allows for a reformulation of interiorization. Interiorization is conceptualized as a continuous series of different, though mutually related movements between self and other and self and self that lead to and are supported by specific formations in language activity: reversion, transposition, and decoupling. Along a short passage of a video-based interview, we trace the reversion of dialogical positions within the addressivity constellation of the two interlocutors, their interactive creation of a heterotopic spacetime, and the decoupling of one speaker's psychological activity from the concrete here-and-now and the present other by moving and acting into this new sphere. Interiorization appears as a movement at the border of past, present, and possible future(s).
Keywords: Interiorization; Dialogical self; Language activity; Voice; Vygotsky; Heterotopia; Video-confrontation

Fachsensibilität als Ressource für den Writing Fellow-Ansatz - Frahnert, Vanessa; Karsten, Andrea (Lehren und Lernen mit Writing Fellows. Beiträge zur Forschung, Evaluation und Adaption)
Vanessa Frahnert und Andrea Karsten stellen ihr Textograph*innen-Programm zur Unterstützung des Schreibens in der Lehre vor, das seit dem Sommersemester 2016 zum regelmäßigen Angebot des Kompetenzzentrums Schreiben der Universität Paderborn gehört. Das Programm baut auf den grundlegenden Prinzipien und Überlegungen des Writing Fellow-Konzepts auf, ist aber an die theoretische Ausrichtung des Schreibzentrums sowie die Gegebenheiten der Universität angepasst. Der Beitrag stellt das Programm und seine theoretischen Hintergründe vor und arbeitet die Unterschiede im Vergleich zum Writing Fellow-Ansatz heraus.